2020
DOI: 10.7717/peerj.8582
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of chocolate spot disease (Botrytis cinerea) in faba bean using endophytic actinomycetesStreptomyces: a field study to compare application techniques

Abstract: Sustainable agriculture is needing economic applications for disease control. One possibility is offered by local medical plants. Endophytes of medical plants, such as actinomycetes Streptomyces sp. have previously shown antagonistic activities against fungal phytopathogens. In the present field experiment, we aimed to verify the efficiency of endophytic Streptomyces against one of the common pathogens, Botrytis cinerea, causing chocolate spot disease for faba bean (Vicia fabae L.). We tested two strains of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“… Antifungal activity (% growth inhibition * ) of actinomycetes in vivo isolated from different environments [ 1 , 4 , 10 , 21 , 25 , 29 , 59 , 60 , 63 , 69 , 70 , 71 , 73 , 74 , 77 , 78 , 80 , 83 , 85 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. …”
Section: Figurementioning
confidence: 99%
“… Antifungal activity (% growth inhibition * ) of actinomycetes in vivo isolated from different environments [ 1 , 4 , 10 , 21 , 25 , 29 , 59 , 60 , 63 , 69 , 70 , 71 , 73 , 74 , 77 , 78 , 80 , 83 , 85 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. …”
Section: Figurementioning
confidence: 99%
“…Asaturova et al (2022), evaluating seed and plant treatment with Bacillus strains against P. tritici-repentis, also observed that the treatment of seeds and plants with strain BZR336 was 10% higher than when treating the plants alone. Other authors also observed that cell-free supernatant of Streptomyces isolates reduced leaf spots of plants infected with Botrytis cinerea and Alternaria brassicicola, and contributed to increased dry weight of plants (El-Shatoury et al 2020;Sharma and Manhas 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Once associated with plant rhizosphere and tissues, actinomycetes counteract microbial phytopathogens by promoting plant growth and development through the solubilization of phosphates, indoleacetic acid, hydrogen cyanide, and ammonia production [59]. Actinomycetes also induce systemic resistance [60], promoting a faster and stronger response of plants to pathogenic attacks [61].…”
Section: Discussionmentioning
confidence: 99%